2018
DOI: 10.1093/cid/ciy595
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Middle East Respiratory Syndrome Coronavirus During the Acute and Convalescent Phases of Human Infection

Abstract: Our findings show an association between the early CD8+ T cell response and the severity of the infection, and also provide basic information that may help to prepare effective control strategies for MERS in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
140
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(155 citation statements)
references
References 34 publications
11
140
0
2
Order By: Relevance
“…[54][55][56] During the acute phase of MERS, robust virus-specific CD8 T-cell responses were detected in most patients with severe or moderate disease, with antibody and CD4 T-cell responses appearing later in the disease course. 57 T-cell and antibody responses were reliably detected 2-3 weeks after diagnosis, although they were detected earlier in some patients. 49,57 Studies of MERS survivors showed that MERS-CoV-specific antibody responses tended to be lower and transient in patients with mild or subclinical disease when compared with patients with severe disease, in whom MERS-CoV-specific antibody responses were detected for at least 2 years.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 90%
See 2 more Smart Citations
“…[54][55][56] During the acute phase of MERS, robust virus-specific CD8 T-cell responses were detected in most patients with severe or moderate disease, with antibody and CD4 T-cell responses appearing later in the disease course. 57 T-cell and antibody responses were reliably detected 2-3 weeks after diagnosis, although they were detected earlier in some patients. 49,57 Studies of MERS survivors showed that MERS-CoV-specific antibody responses tended to be lower and transient in patients with mild or subclinical disease when compared with patients with severe disease, in whom MERS-CoV-specific antibody responses were detected for at least 2 years.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 90%
“…57 T-cell and antibody responses were reliably detected 2-3 weeks after diagnosis, although they were detected earlier in some patients. 49,57 Studies of MERS survivors showed that MERS-CoV-specific antibody responses tended to be lower and transient in patients with mild or subclinical disease when compared with patients with severe disease, in whom MERS-CoV-specific antibody responses were detected for at least 2 years. [57][58][59][60] In contrast, T-cell responses were detected in all MERS survivors for at least 2 years.…”
Section: Protective and Deleterious Immune Responsesmentioning
confidence: 90%
See 1 more Smart Citation
“…According to the statistics provided by the World Health Organization (WHO) on June 10, 2019, a total of 2428 laboratory-confirmed cases of human MERS-CoV infection have been reported, with an estimated 838 deaths in 27 countries. The accumulated evidence suggested that MERS-CoV infections are characterized by high levels of systemic inflammatory cytokines/chemokines as well as immunopathology [4][5][6][7][8][9][10][11]. High inflammatory cytokines and chemokines levels have been strongly correlated with poor disease outcomes, immunopathology and massive infiltration of the immune inflammatory cells into the lungs [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Airway memory T‐cells and viral E protein mutations have been identified in CoV infections as potential targets for vaccine strategies . Immune responses seem to be indicative of disease severity but more studies are needed to have a practical assay for decision making at hand.…”
mentioning
confidence: 99%